Band Gap-Tailored Two-Terminal Lead-Free Germanium- and Tin-Based Single-Halide Perovskite Materials for Efficient Tandem Solar Cells - Mondal S.; Chaudhury M.; Chakrabarti P.; Maity S. (My University, 2025)
Metal halide perovskites owing to their excellent band gap tunability have shown great promise in designing two-terminal tandem solar cells to push the limitations of single-junction devices. However, the use of lead in perovskite absorber layers has raised several questions in this field due to the inherent toxic nature of this element. Moreover, most of the wide-band-gap top absorber layers that are used are composed of mixed halides (mixture of iodine and bromine), leading to halide segregation inside the device and affecting its long-term performance. In order to address these issues, the present work focuses on the simulation of a lead-free, single-halide, all-perovskite two-terminal tandem solar cell with its physical understanding in great detail. A total of 4 different absorber layers and 10 different charge transport layers have been evaluated for bringing out the best device performance. Since the band gap of the absorber layers plays a vital role in determining the efficiency of the overall device, this work also contains a brief summary of the band gap tuning of the perovskite crystal via compositional engineering. It has been observed that methylammonium germanium halide (MAGeI3), having a thickness of 930 nm, is used as a top absorber layer when combined with FA0.75Cs0.25SnI3, which is used as a bottom absorber layer having a thickness of 507 nm; the best-performing tandem device has been obtained with a current density matching of 16 mA/cm2 and a PCE of 29.26%, thus showing a lot of potential for future investigations. © 2023 American Chemical Society.